Filosofi Tengka Dalam Pendidikan Dan Pelatihan - Dwi Permatasari, Intan; Listiana, Heni; Syafiq Fahmi , Ach (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
This research aims to find out the deep meaning of the tengka philosophy in education and training. This research uses a qualitative research method with a library research approach. The data collection technique uses library research, observation and analysis of the scientific references obtained. The results of this research are first, the tengka philosophy, which has a deep meaning related to the concept of steadfastness which comes from moral values, morality and character, secondly, the tengka philosophy in education refers to the application of education, for example in achieving educational goals and in forming character, namely not only educating and teaching students in the knowledge aspect, but also in the moral and skill aspects that need to be taken into account. The three tengka philosophies in training refer to the basic skills possessed by the training participants, both technically and mentally. The training carried out is not only aimed at producing participants who are experts in one field but rather to build character and a positive mindset.